Molecular analysis of receptor protein tyrosine phosphatase mu-mediated cell adhesion. - Aricescu, A; Hon, W; Siebold, C; Lu, W; Van Der Merwe, P; Jones, E (2006)
Type IIB receptor protein tyrosine phosphatases (RPTPs) are bi-functional cell surface molecules. Their ectodomains mediate stable, homophilic, cell-adhesive interactions, whereas the intracellular catalytic regions can modulate the phosphorylation state of cadherin/catenin complexes. We describe a systematic investigation of the cell-adhesive properties of the extracellular region of RPTPmu, a prototypical type IIB RPTP. The crystal structure of a construct comprising its N-terminal MAM (meprin/A5/mu) and Ig domains was determined at 2.7 A resolution; this assigns the MAM fold to the jelly-roll family and reveals extensive interactions between the two domains, which form a rigid structural unit. Structure-based site-directed mutagenesis, serial domain deletions and cell-adhesion assays allowed us to identify the four N-terminal domains (MAM, Ig, fibronectin type III (FNIII)-1 and FNIII-2) as a minimal functional unit. Biophysical characterization revealed at least two independent types of homophilic interaction which, taken together, suggest that there is the potential for formation of a complex and possibly ordered array of receptor molecules at cell contact sites.